Efficacy and Safety of TACE Combined With Lenvatinib Plus PD-1 Inhibitors Compared With TACE Alone for Unresectable Hepatocellular Carcinoma Patients: A Prospective Cohort Study - Qu, Shuping; Zhang, Xiaobing; Wu, Yutian; Meng, Yan; Pan, Hongyu; Fang, Qiang; Hu, Lei; Zhang, Jin; Wang, Ruoyu; Wei, Lixin; Wu, Dong (Frontiers in Oncology, 2022)
Purpose: To compare the efficacy and safety of the combination of transcatheter arterial chemoembolization (TACE), Lenvatinib, and programmed cell death protein-1 (PD-1) inhibitors (combination group) with TACE (TACE group) in the treatment of patients with unresectable hepatocellular carcinoma (uHCC). Methods: We consecutively enrolled 110 patients with uHCC in this prospective cohort study, with 56 patients receiving combination treatment and 54 patients receiving TACE from November 2017 to September 2020. The differences in tumor response, survival benefit, and adverse events (AEs) were compared between the two groups. Factors affecting survival were identified via Cox regression analysis. Results: Compared with the TACE group, the combination group had a higher objective response rate (ORR) (67.9% vs. 29.6%, p < 0.001), longer median progression-free survival (mPFS) (11.9 vs. 6.9 months, P = 0.003) and overall survival (mOS) (23.9 vs. 15.3 months, p < 0.001). Multivariate analysis showed that the neutrophil-to-lymphocyte ratio (NLR) and the treatment option were independent factors associated with the PFS and OS. Further subgroup analysis showed that patients with low NLR (≤median 3.11) receiving combination therapy had better mPFS (20.1 vs. 6.2 months, P < 0.001) and mOS (28.9 vs. 15.2 months, P < 0.001) than those receiving TACE, while no obvious difference in PFS or OS was observed between the two groups in patients with high NLR (> 3.11). There were no unexpected toxicities in the combination group. Conclusion: Compared with TACE, the combination treatment demonstrated an improved clinical efficacy and manageable safety profile in patients with uHCC. Combination treatment showed better therapeutic efficacy in patients with low NLR; therefore, this ratio could be used to identify patients who will benefit from this treatment.